The effect of varying collimator geometry in alpha spectrometry of environmental analysis. (November 2020) - Amoah, P A; Pripachkin, D A
Abstract: Assessment of radioactive aerosols in the atmosphere has always been an important field of study due to its effects on many biological systems. The efficiency in measuring these aerosols is therefore critical to research and industrial practice, thus; the principles and methods of geometry development to improve efficiency and resolution is paramount. The aim of this study is to use numerical simulation with MATLAB to improve the resolution and detection efficiency of an alpha spectrometer with varying collimator geometries. A collimator between a radiation source and a detector plays a very important role in identifying specific radionuclides among various species in a radioactive environment. The geometric model of the collimator being considered here is that of a triangular and a hexagonal shape. To evaluate the counts, randomly obtained data using Microsoft excel was used, considering the specified boundary conditions in a two-dimensional plane. Various counts ranging from 100 to 100, 000 were analyzed to obtain the results of a log efficiency curve using MATLAB. Subsequent counting efficiency curves were then determined relative to the dimensions. An average value of 0.44 ± 0.1106 was determined for the efficiency. With emphases on the apothem of the geometries being studied, the triangular shaped collimator has theoretically shown to produce a higher resolution though with a possible decrease in detection efficiency.